1996
DOI: 10.1161/01.hyp.28.3.478
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of 11β-Hydroxysteroid Dehydrogenase Type 2 (HSD11B2) Flanking Microsatellites With Essential Hypertension in Blacks

Abstract: 11 beta-Hydroxysteroid dehydrogenase type 2 (11 beta-HSD2) specifically modulates access of the mineralocorticoid aldosterone to the kidney mineralocorticoid type 1 receptors in a physiological environment in which there is a molar excess of cortisol. Cortisol and aldosterone have similar affinities for mineralocorticoid receptors. Mechanistically, 11 beta-HSD2 converts cortisol to cortisone. The other known isoform, 11 beta-HSD1, not only catalyzes the cortisol to cortisone reaction but also the reverse react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…Homozygous carriers of the G534 allele had an age, sex and BMI adjusted OR for hypertension of 1.8 (95%CI = 1.0-3.3) compared with carriers of the other genotypes. The microsatellite marker D16S496 flanking the 11BHSD2 gene, which has earlier been reported to be associated with primary hypertension in blacks, 19 was not associated with hypertension in our study population. There was no linkage disequilibrium between the G534A-and D16S496 markers.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…Homozygous carriers of the G534 allele had an age, sex and BMI adjusted OR for hypertension of 1.8 (95%CI = 1.0-3.3) compared with carriers of the other genotypes. The microsatellite marker D16S496 flanking the 11BHSD2 gene, which has earlier been reported to be associated with primary hypertension in blacks, 19 was not associated with hypertension in our study population. There was no linkage disequilibrium between the G534A-and D16S496 markers.…”
Section: Discussionsupporting
confidence: 39%
“…The fragments were separated on agarose gels after staining with ethidium bromide and visualised under ultraviolet light. A gene segment surrounding the D16S496 microsatellite marker 19,22 was amplified with PCR using a 5Ј-end ␥-32 P-ATP labelled (Amersham, Sweden AB, Solna, Sweden) forward primer (5Ј-TAGTAATAGGATCATACTACTTG) and a reverse primer (5Ј-ATAAGCCACTGCGCCCATC). The primers were designed according to the published genomic sequence surrounding D16S496.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] A recent study identified the first naturally occurring polymorphisms in the human HSD11B2 promoter region, with differences in the frequency of polymorphisms between ss and sr subjects. 8 In sum, 11b HSD2 is presumably involved in hypertension as well as in SS, but with a different genetic contribution with respect to the polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…One study has reported an association between a microsatellite marker close to the HSD11B2 gene and hypertension in African Americans with hypertensive end stage renal disease (42). These data were confirmed using a polymorphic restriction site in exon 3 of the HSD11B2 gene.…”
Section: -Hsd2 and "Essential" Hypertensionmentioning
confidence: 85%